Angiotensin II receptor blocker valsartan enhances glucose-induced insulin secretion - Ayob, Azizi; Hashim, Suhaimi; Azdan, Zulnizam; Abdul Razak, Tariq (Islamic World Academy of Sciences, 2006)
A number of antihypertensive drugs are known to be diabetogenic. This may contribute to less than expected decrease in the incidence of coronary heart disease with reduction in blood pressure with treatment in hypertensive patients. This study was aimed to determine the effects of a member, Valsartan, of a new class of drugs, angiotensin II receptor blocker, on glucose induced insulin secretion. Male albino rat pancreases were used. The isolated ancreases were perfused with Kreb's solution containing bovine albumin (200 mg/dl) with low glucose (60 mg/dl) followed by high glucose (300 mg/dl) at a rate of 4 ml/min. The dose of Valsartan used was based on the peak plasma level achieved in human at standard single oral dose of 80 mg daily, which was 1.64 mg/L. Five treatment groups were used: Control group, Valsartan at 10%, Valsartan at 100% and Valsartan at 10 times of the 1.64 mg/L, and Diazoxide 10 μg/ml group. Insulin levels in the perfusate were measured by radioimmunoassay. Valsartan at all concentrations significantly increases glucose induced insulin secretion (p < 0.05). Valsartan at 10 %, Valsartan at 100% and Valsartan at 10 times of the 16.4 mg/L, increases glucose induced insulin secretion by 226.4 %, 161.7 % and 156.3 %, respectively. Diazoxide, significantly inhibits glucose induced insulin secretion (p < 0.05). Valsartan at all concentrations enhances glucose-induced insulin secretion in isolated rat pancreas technique.